Observing Higgs dark matter at the CERN LHC - Alves, Alexandre [UNESP] (American Physical Society (APS), 2010)
Triggering the electroweak symmetry breaking may not be the only key role played by the Higgs boson in particle physics. In a recently proposed warped five-dimensional SO(5) - U(1) gauge-Higgs unification model, the Higgs boson can also constitute the dark matter that permeates the universe. The stability of the Higgs boson in this model is guaranteed in all orders of perturbation theory by the conservation of an H-parity quantum number that forbids triple couplings to all standard model (SM) particles. Such a unique feature of the model shows up as a delay in the restoration of the tree-level unitarity, which in turn enhances the production cross section as compared to the standard model analogue. Recent astrophysical data constrain the mass of such a Higgs dark matter particle to a narrow window of 70-90 GeV range. We show that the Large Hadron Collider can observe these Higgs bosons in the weak boson fusion channel with about 260fb⊃-1 of integrated luminosity in that mass range. © 2010 The American Physical Society.